The Importance of the Intellectual Capital-Based Model of Islamic Microfinance in India - Rusni HASSAN; Syed Ahmed SALMAN; Adnan YUSOFF (Communications of International Proceedings, 2020)
Microfinance has existed in the history of India for over a century and proves to be one of the most significant tools towards poverty alleviation. The Indian microfinance institutions (MFI’s) have attained an outreach of over 30 million clients. A large portion of the population is still not catered making India a favorite market for Microfinance programs. The Sachar Committee Report stated that out of India’s poor the deeply impoverished is the Muslim population who also suffer from huge illiteracy, a high drop-out rate, depleting asset base, below-average work participation, and lack of stable and secure employment. Traditional microfinance has not been able to solve the poverty alleviation problem of the Muslims who stay away from conventional microfinance due to religious reasons. Also, the Interest-free microfinance has not been of much use due to its limited availability and scope of operation. The number of customers of IMFIs has quadrupled in recent years but still has only managed to reach one million Muslims compared with 650 million Muslims who are below the average poverty line. However, Intellectual capital based Islamic microfinance seems to be a way out because it does not only deliver the microcredit to the destitute but also provides technical and professional support. Moreover, it eases the securing of finance by making use of social collateral instead of a physical one. This study investigates the importance of the intellectual capital-based model of Islamic microfinance in India. The study will concentrate mainly on social capital, human capital, and spiritual capital. It is hoped that the study will be significant to Muslim communities as the conventional microfinance products have just worked on the surface and have not been able to address the needs of Muslim clients.
Keywords: Islamic Microfinance; Intellectual capital; Social capital; Human capital & Spiritual capital